Human milk bank in a rural setup - A success story - Bhavana Lakhkar; Sachin Damke; Revatdhamma Meshram (Wolters Kluwer Medknow Publications, 2022)
Background: This article describes the experience of a rural human milk bank, with the problems faced in first 6 months including the coronavirus disease (COVID) crisis and interventions leading to success. Methods: The study included individual counselling by dedicated counsellors, focused counselling of primipara mothers seeking the help of obstetricians, counselling of pre-term mothers by neo-natal nurses, periodically delivered information in post-natal wards, and counselling of grandmothers and husbands. Results: The COVID crisis was dealt with donations from reverse transcriptase-polymerase chain reaction-negative mothers with social distancing and mask use. Younger, educated, working mothers with normal delivery and from middle-income families were easy to counsel. Periodic announcements in wards significantly increased awareness about milk banks and donation. Pre-term mothers could be motivated when their baby was nil by mouth or they saw other babies in need of milk. Lactation support to mothers with breast problems, especially in primipara, helps in getting more donors. Counselling of fathers was easier than that of grandmothers. Conclusions: Structured awareness programs and counselling strategies along with education of grandmothers and husbands were very effective in increasing human milk donation.